MEANING AND SIGNIFICANCE OF FEASTS AND FESTIVALS IN HUMAN SOCIETY - Michael, S M (Journal of Dharma, 2003)
There is a growing trend in anthropology to understand humankind through its experience. The anthropology of experience deals with how individuals actually experience their culture. In almost all cultures, life is experienced as pulsating and rhythmical. It is a combination of breaks and reunions. Rituals and rites are the means by which these experiences of life are communicated. Hence, experiences of humankind are heavily embedded in cultural symbols, particularly those of feasts, festivals, rituals, celebrations and other powerful performative genres.